A network pharmacology approach to evaluate the synergistic effect of dihydromyricetin and myricitrin in vine tea on the proliferation of B16F10 cells - Zhao, Nanxing; Kong, Hongming; Liu, Hesheng; Shi, Qing; Qi, Xiangyang; Chen, Qiuping (Frontiers in Nutrition, 2022)
Aim of the study: Although vine tea has demonstrated broad-spectrum anti-cancer properties, its main active compounds, dihydromyricetin (DMY) and myricitrin (MYT), exert weaker effects than the tea extracts. This study aimed to investigate the synergistic inhibitory effects of DMY and MYT on B16F10 cell proliferation and their synergistic inhibitory effects. Methods: The effect of vine tea extracts (VTEs) and their active compounds on B16F10 cells was analyzed by MTT assay, fluorescence staining, and flow cytometry. The synergistic effects were calculated by the combination index (CI), and its mechanism was discussed by network pharmacology. Results: Different VTEs varied in their inhibition of B16F10 cell growth, with IC50 values ranging from 4.45~12.95 μg/mL, Among these, Guangzhou Qingyuan (Level 2), appeared to have the most potent inhibitory effect. The IC50 value of mix-use of DMY and MYT was 19.94~64.4 μM, of which DMY:MYT=8:1 had the minimum IC50 value of 19.94 μM. Combinations in the 1:1~8:1 range had stronger effects than the isolated active compound. When they were mixed at the ratio of 1:4~8:1, CI <1, showing a synergistic effect. The combination of DMY and MYT also significantly inhibited the tyrosinase activity in B16F10 cells, consistent with its impact on cell proliferation. The eight potential targets were identified by network pharmacology regulating melanin metabolism, tyrosine metabolism, and melanogenesis signaling. According to the analysis of protein-protein interactions, TP53, TNF, and TYR might be critical targets for preventing and treating melanoma. Conclusion: We found that DMY and MYT induced apoptosis of B16F10 cells, and their combined application had a significant synergistic effect. The present findings indicated that vine tea had a multi-pathway and multi-target impact on the prevention and treatment of melanoma.